Patterns and predictors of periodontal disease and tooth loss among users of smokeless tobacco - Syed Muazzam Nasir; Tajwer Sultana; Shahkamal Hashmi; Mansoor Ahmed (BMC, 2023)
Abstract Background Smokeless tobacco (SLT) products of several different types are widely used in several South Asian countries including Pakistan. These products are consumed in different forms and with different names. The study aims to determine adverse effects of the SLT consumption on periodontal tissues. Methods This cross sectional study was conducted in Karachi, Pakistan. It recruited 377 users of (SLT) with 231 males (61.3%) and 146 females (38.7%) of age 15 to 45 years. After obtaining informed consent, quantitative data were collected via a questionnaire followed by intra oral clinical examination to determine presence of periodontal diseases using community periodontal index (CPI). To determine the association between periodontal diseases and smokeless tobacco consumption habits, Chi Square test was conducted. Results Gingival recession (Class II-IV) (65.8%) was the most prevalent periodontal disease among SLT users. CPI score was high (CPI score 3 and 4) in 31.3% participants, whereas tooth loss was found in 21%. Among types of SLT products, gutka (28.6%) and betel quid (23.3%) were most commonly used. Using SLT for five or more years was found to be associated with a high CPI score, gingival recession (Class II-IV), moderate to severe tooth mobility, and presence of tooth loss. Conclusions The study found statistically significant association between duration in years of using SLT and periodontal disease including gingival recession, tooth mobility and tooth loss. However, no significant results were found between retention during single use and frequency of SLT use per day. However, the link of these factors with the periodontal disease cannot be eliminated.